1992
DOI: 10.2307/3869522
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Abnormal Development in the Arabidopsis Vegetative Shoot Apex

Abstract: Vegetative development in the Arabidopsis shoot apex follows both sequential and repetitive steps. Early in development, the young vegetative meristem is flat and has a rectangular shape with bilateral symmetry. The first pair of leaf primordia is radially symmetrical and is initiated on opposite sides of the meristem. As development proceeds, the meristem changes first to a bilaterally symmetrical trapezoid and then to a radially symmetrical dome. Vegetative development from the domed meristem continues as le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 0 publications
1
63
0
Order By: Relevance
“…We tested the growth conditions described in their Commentary, which involve the use of 24-well plates, and found that the seedlings were stressed and exhibited delayed development compared with ours, which might explain the severely retarded shoot development in their CLV3p-treated seedlings and the relatively flat SAM they observed even in clv3 seedlings. Furthermore, our seedlings were grown in liquid medium at higher temperature (27˚C compared with 22˚C) and constant light (compared with 16-h light) during bacterial infection, which likely explains the more advanced SAM development in wild-type and clv3 seedlings that we observe (Medford et al, 1992;Bowman, 1993;Fiers et al, 2006;Kinoshita et al, 2010;Lee et al, 2011) but was not observed by Segonzac et al (2012).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…We tested the growth conditions described in their Commentary, which involve the use of 24-well plates, and found that the seedlings were stressed and exhibited delayed development compared with ours, which might explain the severely retarded shoot development in their CLV3p-treated seedlings and the relatively flat SAM they observed even in clv3 seedlings. Furthermore, our seedlings were grown in liquid medium at higher temperature (27˚C compared with 22˚C) and constant light (compared with 16-h light) during bacterial infection, which likely explains the more advanced SAM development in wild-type and clv3 seedlings that we observe (Medford et al, 1992;Bowman, 1993;Fiers et al, 2006;Kinoshita et al, 2010;Lee et al, 2011) but was not observed by Segonzac et al (2012).…”
mentioning
confidence: 92%
“…In their Commentary, Segonzac et al (2012) report that they were not able to observe the characteristically enlarged vegetative SAM and Pseudomonas syringae pv tomato (Pst) DC3000-GFP (for green fluorescent protein) infection in the clv3 seedlings (Medford et al, 1992;Bowman, 1993;Fiers et al, 2006;Kinoshita et al, 2010;Lee et al, 2011) and argue from first principles that it would not be possible for P. syringae to infect the SAM. However, Segonzac et al (2012) used very different conditions for growing seedlings when they attempted to repeat our bacterial infection experiments.…”
mentioning
confidence: 99%
“…ago1 mutants exhibit numerous phenotypic abnormalities such as radialized leaves, abnormal infertile flowers with filamentous structures resembling small squid (thus the name Argonaute), and in some cases shoot apical meristem defects (Bohmert et al 1998;Lynn et al 1999). It should be noted that mutants affecting the shoot apical meristem, around which leaves are initiated and patterned, are known to produce abnormal leaf phenotypes (Medford et al 1992). AGO1 was subsequently shown to be necessary for post-transcriptional silencing of transgenes as well as for cosuppression of transgenes and their corresponding homologous endogenous genes (Fagard et al 2000).…”
Section: The Argonaute Familymentioning
confidence: 99%
“…The fifth and sixth leaves of the rosette represent the first consistently adult leaves of the Ler strain (as defined for the Wassilewskija strain by Medford et al, 1992). Under the culture conditions used, individual leaves progressed through full expansion to maturity followed by a period of progressive leaf yellowing and, finally, a degeneration and complete desiccation of the tissue.…”
Section: Life History Traits In Arabidopsismentioning
confidence: 99%